Characterization of fully silicided source/drain SOI UTBB nMOSFETs at cryogenic temperatures. (June 2022) - Han, Yi; Xi, Fengben; Allibert, Frederic; Radu, Ionut; Prucnal, Slawomir; Bae, Jin-Hee; Hoffmann-Eifert, Susanne; Knoch, Joachim; Grützmacher, Detlev; Zhao, Qing-Tai
Highlights: SOI UTBB nMOSFETs are operated at cryogenic temperature with different gate lengths. The impact of the back-gate on the device performance is systematically studied. A good performance of devices is obtained at cryogenic temperature by back-gate. Short channel effects are investigated at cryogenic temperature. Abstract: In this paper we present an experimental study of SOI UTBB n-MOSFETs at cryogenic temperatures. The device employs fully silicided source/drain with dopant segregation formed by "Implantation Into Silicide" (IIS) process. The impact of the back-gate (Vback ) on the device performance is systematically investigated. The results demonstrate that Vback is essential to tune the threshold voltage Vth. And optimization of Vback values can improve the subthreshold swing (SS), Drain-Induced Barrier Lowering (DIBL), transconductance Gm and mobility at cryogenic temperatures, providing a potential to fulfill the ultra-low power requirement for quantum computing application.